2021
DOI: 10.1007/s11071-021-06836-y
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the computational analysis of SARS-COV2 genome

Abstract: Given a data-set of Ribonucleic acid (RNA) sequences we can infer the phylogenetics of the samples and tackle the information for scientific purposes. Based on current data and knowledge, the SARS-CoV-2 seemingly mutates much more slowly than the influenza virus that causes seasonal flu. However, very recent evolution poses some doubts about such conjecture and shadows the out-coming light of people vaccination. This paper adopts mathematical and computational tools for handling the challenge of analyzing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Furthermore, our platform is able to isolate the rare SARS-CoV-2 NP-specific clones, which typically recognize immunosubdominant epitopes. Owing to 90% homology between SARS-CoV-2 and SARS-CoV NP [ 32 , 33 ], many SARS-CoV-2 NP-binding antibodies cross-reacted SARS-CoV NP as well. Indeed, previously isolated antibodies from SARS-CoV NP-immunized mice were also reactive to SARS-CoV-2 , supporting that conserved epitopes between two viral NPs were immunodominant.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our platform is able to isolate the rare SARS-CoV-2 NP-specific clones, which typically recognize immunosubdominant epitopes. Owing to 90% homology between SARS-CoV-2 and SARS-CoV NP [ 32 , 33 ], many SARS-CoV-2 NP-binding antibodies cross-reacted SARS-CoV NP as well. Indeed, previously isolated antibodies from SARS-CoV NP-immunized mice were also reactive to SARS-CoV-2 , supporting that conserved epitopes between two viral NPs were immunodominant.…”
Section: Discussionmentioning
confidence: 99%
“…Odagaki 26 demonstrated that the oscillation of the infection curve could be self‐organized in the SIQR model, in which the net rate of change was a function of the number of infected individuals. Other approaches to the SARS‐CoV‐2 infection can be found in Tenreiro et al 27 (and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…During the past few decades, various scientific approaches and mathematical methods were developed and applied to model the dynamics of the spread of infectious diseases [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Numerous studies have also examined the dynamics of SARS [ 21 , 22 , 23 , 24 ] and COVID-19 [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%